Evaluation of FT - Raman and FTIR – ATR spectroscopy for the quality evaluation of Lavandula spp. Honey - Anjos, O. (2021)
Mono ﬂ oral Lavandula spp. honey is very appre - ciated by consumers due to its characteristic and pleasant aroma and ﬂ avor. Given the economic importance of this type of honey, it is important to develop a rapid and non - expensive methodology that allows certifying its quality. In this context, this study aimed to compare the applic - ability and accuracy of FTIR - ATR and FT - Raman techni - ques for the quality evaluation of Lavandula spp. honey. Calibration models, with PLS regression models, were obtained for both methodologies concerning the following parameters: total acidity, reducing sugars, hidroximetil - furfural ( HMF ) , electrical conductivity, ash, proline con - tent, diastase activity, apparent sucrose, total ﬂ avonoids, and total phenolic contents. The calibration models had high regression coe ﬃ cients, r 2 ( FTIR - ATR: 0.965 – 0.996; FT - Raman: 0.983 – 0.999 ) , high ratios of performance to deviation, RPD ( FTIR - ATR: 5.4 – 15.7; FT - Raman: 7.6 – 53.7 ) , and low root mean square errors ( RMSEs; FTIR - ATR: 0.005 – 3.0; FT - Raman: 0.004 – 1.02 ) . These results corrobo - rate the potentiality of FTIR - ATR and FT - Raman for quality evaluation and evaluation of the chemical properties of Lavandula spp. honey even though FT - Raman technique provided more accurate models.